Strategi Pemasaran Melalui Jaringan Bisnis Untuk Meningkatkan Penjualan Buku Do’a Pada Percetakan CV. Aslan Grafika - Resya Dwi Marselina; Alya Putri Agustina; Indah Siti Aulya; Juliana Juliana; Nirmala Nurdiandani; Ulfiana Hanifah (Universitas 17 Agustus 1945 Semarang, 2023)
Business has an important role in society. One of significant factor influencing the sustainability of a business is through business networks. With the establishment of business networks, information can be spread quickly (Wiharjo, 2012). Business networking is very important for business, including printing business. Printing is an attempt to mass produce writing and images using a printing press. (Nggaibo, 2021). Printing business is one of the fastest growing businesses. CV. Aslan Grafika is a printing business located in Banjaran, Bandung, West Java. The reason the author conducted Business Network research on CV. Aslan Grafika because author is interested in marketing strategies undertaken by CV. Aslan Grafika thus became the pioneer of printing in Banjaran area which provides many printing services. This research aims to determine the business network used in CV. Aslan Grafika and how the influence of this business network on the performance of printing, especially manufacture and sale of books du'a Hajj and umrah which is the main highlight of the author in this study. The type of research used is descriptive qualitative. The data source used consists of primary and secondary data. Data collection techniques are interview techniques. Data analysis techniques used are qualitative data analysis techniques.